8q-5=5q+3

Simple and best practice solution for 8q-5=5q+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8q-5=5q+3 equation:


Simplifying
8q + -5 = 5q + 3

Reorder the terms:
-5 + 8q = 5q + 3

Reorder the terms:
-5 + 8q = 3 + 5q

Solving
-5 + 8q = 3 + 5q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-5q' to each side of the equation.
-5 + 8q + -5q = 3 + 5q + -5q

Combine like terms: 8q + -5q = 3q
-5 + 3q = 3 + 5q + -5q

Combine like terms: 5q + -5q = 0
-5 + 3q = 3 + 0
-5 + 3q = 3

Add '5' to each side of the equation.
-5 + 5 + 3q = 3 + 5

Combine like terms: -5 + 5 = 0
0 + 3q = 3 + 5
3q = 3 + 5

Combine like terms: 3 + 5 = 8
3q = 8

Divide each side by '3'.
q = 2.666666667

Simplifying
q = 2.666666667

See similar equations:

| 2y+y-.5=23.5 | | 11-9=-23 | | X+6*4=126 | | 8x=4x-6 | | .4x^2+.2=x | | x-6-7=26(x-7) | | -8x-x=99 | | 6n+2=n+8 | | 2(9c-6)=14 | | -4m-2=82 | | -8(n-7)+3(n-3)=41 | | (9x+y)+(3x+2y)=180 | | -8(n-7)+3(n-3)=31 | | 64=8w-8 | | 2N+7(9N+10)= | | 6+.010x=0.15x+8 | | 4p+2=p+4 | | -5y-5(-62y)=0 | | 13.33+.11x=13.83+.08x | | 14a+5=33 | | -8(b+2)=32 | | 3.25x+5.50y=112.4 | | 93=2x-3(-2x-7) | | 4x+y=108 | | (3x+6)-(-6x-7)=4(3x+7) | | 7m+4=4m-5 | | 8b+-7=7b+2 | | 2x-4-8x=14 | | 5-6x-7=-1-5x | | 4.5=40.05 | | x^4=39.0625 | | S=pirs+pir^2 |

Equations solver categories